Management Strategies in the Production of Service: A Study of Hotel Practice in Southeast Asia - Nankervis, Alan (School of Management, Curtin University of Technology, Perth, Western Australia and the Singapore Human Resources Institute, 1995)
This paper explores the service quality, productivity and human resource management practices of a selection of Southeast Asia hotels, in an attempt to elicit common themes for successful international hotel management. It compares the practices used in different cultural and employment settings with contemporary Australian management styles.